Teach Primary : Observer Manual - World Bank (Washington, DC : World Bank, 2022)
Teach is an open access classroom observation tool that provides a window into one of the less explored and most important aspects of student learning, what goes on in the classroom. The tool has been designed to help countries track and improve teaching quality. In 2020-2021, the Teach Primary tool underwent a review and revision process to strengthen the way it captures inclusive teaching practices. Since its launch, Teach Primary has been used to support the way countries track and improve teaching practices, adapted to each country’s context and needs. This checklist is a proposed addition to be used together with the Teach Primary classroom observation tool; while its use together with the classroom observation component is suggested, it is not mandatory. The aim of the checklist is to assess additional elements related to educational quality, including but not limited to the accessibility of the physical environment. Items indicated with an asterisk are to be asked to the teacher.